FORMULATION OF SLOW RELEASE COMPRESSED FERTILIZER AND INITIAL DESIGN FOR PRODUCTION SYSTEM - Mohd Radzi, H.C.D. (2017)
A flexible layout is one that maintains low material handling costs despite fluctuations in the product demand levels. We extend existing procedures for design of flexible layouts by explicitly capturing the stochastic nature of product demands and the resulting variability in material flows between different processing departments, allowing for the possibility of multiple processing departments of the same type to exist in the same facility, and letting material flows between pairs of individual departments be determined simultaneously with the layout and as a function of demand scenarios. Optimal and heuristic methods are presented for generating flexible layouts and determining flow allocations under various design and operation assumptions. The ability to design and operate manufacturing facilities that can quickly and effectively adapt to changing technological and market requirements is becoming increasingly important to the success of any manufacturing organization. In the face of shorter product life cycles, higher product variety, increasingly unpredictable demand, and shorter delivery times, manufacturing facilities dedicated to a single product line cannot be cost effective any longer. Investment efficiency now requires that manufacturing facilities be able to shift quickly from one product line to another without major retooling, resource reconfiguration, or replacement of equipment. Investment efficiency also requires that manufacturing facilities be able to simultaneously make several products so that smaller volume products can be combined in a single facility and that fluctuations in product mixes and volumes can be more easily accommodated.